Possible relations between arterial hypertension and cervical spine fibromyalgias (literature review) - Alla Kovaleva; Igor Khudetskyy; Oleksandra Kovalyova (Bogomolets National Medical University, 2022)
The literature review analyses and systematises currently available information on fibromyalgia etiology and pathogenesis, hypertension classification and causes, and considers possible relationships between cervical fibromyalgia and hypertension. Statistical data on mortality in Ukraine related to cardiovascular diseases, including hypertension, are highlighted. A concise classification of arterial hypertension according to the International Classification of Diseases-10 (ICD-10) and the International Classification of Diseases-11 (ICD-11) is provided, and its pathogenesis (emission hypertension, resistance hypertension and hypervolemia) is outlined. Physiological relations between cervical spine and cardiovascular system are considered. The main diagnostic criteria for fibromyalgia classification and its development stages are described. Prevalence of fibromyalgia is identified and its forms are classified in accordance with ICD-11. The available data on the likely causes of fibromyalgia pain and any established mechanisms of fibromyalgia pathogenesis, including, but not limited to peripheral and central sensitisation, neurogenic inflammatory processes occurring in the disease-associated peripheral tissues, spinal cord and brain, as well as potential involvement of genetic, endocrine, psychopathological factors and sleep disorders in fibromyalgia development are discussed. The current formal criteria for fibromyalgia classification (revised in 2016), together with assessment of the main pharmacological and non-pharmacological fibromyalgia treatment methods and approaches based upon available published clinical trials outcomes are described. The main directions of fibromyalgia research are identified, and further prospective studies covering different relationship aspects between hypertension and cervical fibromyalgia are evaluated. Among the available literature sources, the only study of patients with comorbid fibromyalgia (fibromyalgia was diagnosed using 1990 American College of Rheumatology criteria and evaluated by Revised fibromyalgia impact questionnaire (FIQR)) and hypertension (blood pressure levels were assessed using the WHO protocol) has been reported. However, this group has only studied the dynamics of changes in cortisol, melatonin and serotonin blood levels, which accompany these pathologies, and these authors have found that fibromyalgia tender points' quantity and FIQR scores are much higher in hypertensive patients with fibromyalgia in comparison with the rest, which has led them to the conclusion that hypertension prevalence in patients with fibromyalgia could be related to fibromyalgia severity. Thus, this thorough literature review demonstrates that clinical studies examining possible relationships between hypertension and cervical spine fibromyalgia are at lack and require further considerations.